Optogenetic Stimulation of Lateral Amygdala Input to Posterior Piriform Cortex Modulates Single-Unit and Ensemble Odor Processing - Sadrian, Benjamin; Wilson, Donald A. (Frontiers in Neural Circuits, 2015)
Olfactory information is synthesized within the olfactory cortex to provide not only an odor percept, but also a contextual significance that supports appropriate behavioral response to specific odor cues. The piriform cortex serves as a communication hub within this circuit by sharing reciprocal connectivity with higher processing regions, such as the lateral entorhinal cortex and amygdala. The functional significance of these descending inputs on piriform cortical processing of odorants is currently not well understood. We have employed optogenetic methods to selectively stimulate lateral and basolateral amygdala (BLA) afferent fibers innervating the posterior piriform cortex (pPCX) to quantify BLA modulation of pPCX odor-evoked activity. Single unit odor-evoked activity of anaesthetized BLA-infected animals was significantly modulated compared with control animal recordings, with individual cells displaying either enhancement or suppression of odor-driven spiking. In addition, BLA activation induced a decorrelation of odor-evoked pPCX ensemble activity relative to odor alone. Together these results indicate a modulatory role in pPCX odor processing for the BLA complex, which could contribute to learned changes in PCX activity following associative conditioning.